ENTREPRENEURIAL EDUCATION STRATEGY TO PROMOTE CREATIVITY AND INNOVATION OF ENGLISH AS FOREIGN LANGUAGE (EFL) STUDENTS - Gunawan, Gunawan; Sarmadani, Sarmadani; Noni, Nurdin; Jafar, Muhammad (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This research examines Entrepreneurial Education Strategy to Promote Creativity and Innovation of EFL Students. The study aims to know about the strategies used by lecturers to promote students' creativity and innovation in entrepreneurship, and find how entrepreneurial education effects of EFL students at the institution. The study employs a qualitative descriptive method, utilizing interviews with entrepreneurship lecturers as data collection techniques. This study involved five purposefully selected lecturers. Based on the results obtained, it shows that there are five strategies used to promote students' entrepreneurial innovation and creativity that are 1) Students are motivated to become entrepreneurs after taking entrepreneurship courses. 2) Student apprenticeship program in the business world. 3) Establishing collaboration with business institutions. 4) Providing motivation to students to take part in competitions and entrepreneurial program grants. 5) Establishment of campus entrepreneurship study centers, such as student cooperatives, and student business units. The last, as a result, entrepreneurship education has a highly beneficial and amazing impact on enhancing students' entrepreneurial innovation and creativity. Thus, the entrepreneurial education strategy effectively boosts student creativity and innovation, transforming mindsets and preparing them for business pursuits. This research highlights the gap in understanding the relationship between education, experience, the level of education, and entrepreneurial intentions.